25 Waves of the German Socio-Economic Panel (SOEP): An Asset to Inter-disciplinary Research - Gisela Trommsdorff (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The German Socio-Economic Panel Study (SOEP) has been providing representative data records on the population in Germany in annual surveys since 1984, i.e., for almost 25 years. With the 2008's fieldwork, 25 waves have been completed. The SOEP expanded to include a sample from East Germany in 1990 as well as to include special samples on immigration and high-income households. Looking back over 25 years of scientific activity is, for an institution, which is what SOEP has become, also an opportunity to examine its original purpose and resources, the development steps and results that followed, and its current aims.
Keywords: 330